Monitoring Perkembangan Program Bank Sampah Menggunakan Tableau Public di RW 05 Kelurahan Cipinang Besar Selatan - Tri Wahyudi; Diky Pramudita; Fadillah Abi Prayogo; Muhammad Rizky Julianto; Zahra Purwanti (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This community service focuses on managing the Waste Bank in RW 05, Cipinang Besar Selatan Subdistrict with the aim of overcoming the lack of public interest in the Waste Bank program. Through a mentoring approach using Tableau Public, this activity aims to increase public understanding of the program. By using qualitative analysis, the results of the waste movement dashboard visualization are expected to provide an understanding of the influence of the Waste Bank on increasing waste volume. The research results show that data visualization using Tableau Desktop successfully achieved service objectives, providing significant insight into the effectiveness and development potential of the Waste Bank program. Features such as Total Waste per Month, Top Customer Rank, Top District, Top Types of Waste, and RT Participation provide an in-depth understanding of program dynamics. Data visualization has succeeded in increasing public interest, effectively reducing environmental pollution, and providing transparency of contributions, positive comparisons, personal understanding of environmental impacts, and motivation through growth and achievement. Therefore, the use of Tableau data visualization in the Waste Bank program is not only a data management tool, but also a driver of active participation and public awareness of the importance of protecting the environment. The Waste Bank program supported by data visualization has great potential to achieve sustainability goals and reduce negative impacts on the environment.